English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-30 10:56:15 · 2 answers · asked by Matty B 3 in Science & Mathematics Mathematics

2 answers

either
f(x)= x²-4x+4-4= x²-4x
f'(x)=2x-4

or

f'(x)=2(x-2) from the chain rule

2007-09-30 11:00:55 · answer #1 · answered by chasrmck 6 · 0 0

Use power rule
f'(x) = 2(x-2) = 2x-4

You could verify this by expanding f(x) to x^2-4x+4-4=
x^2-4x. so dy/dx = 2x-4

2007-09-30 18:02:45 · answer #2 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers